alguém desenrola essa aí?
Anexos:
![](https://pt-static.z-dn.net/files/d70/39d70c10873c502f722127714685bfb9.jpg)
Soluções para a tarefa
Respondido por
1
Resposta:
Explicação passo-a-passo:
(√5+x)²=(7-√20-x)²
X+5=49-14√20-x+20-x
X+5=69-14√20-x-x
14√20-x=69-x-x-5 (÷2)
(7√20-x)²=(32-x)²
49(20-x)=1024-64x+x²
980-49x-1024+64x-x²=0
-44+15x-x²=0
X²-15x+44=0
X(x-4)-11(x-4)=0
X-4=0
X=4
X-11=0
X=11
Respondido por
1
(√(x+5) + √(20-x))² = 49
(x+5 + 20 - x + 2√(x+5)(20-x)) = 49
(25 + 2√(20x-x²+100-5x) ) = 49
25 + 2√(15x-x²+100) = 49
2√(15x-x²+100) = 49-25
√(15x-x²+100) = 24/2
√(15x-x²+100) = 12
(15x-x²+100) = 144
15x-x²+100-144=0
-x²+15x-44=0
x =( -15 +/- √(225-4*(-1)*(-44)))/-2
x = (-15 +/- √49)/-2
x = (-15 +/- 7)/-2
x1 = (-15 + (-7))/-2 = (-15 -7)/-2 = -22/-2=11
x2 = (-15 -(-7))/-2 = (-15+7)/-2 =-8/-2 = 4
Perguntas interessantes
ENEM,
10 meses atrás
Matemática,
10 meses atrás
Português,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
História,
1 ano atrás